The necrotrophic effector SnToxA induces the synthesis of a novel phytoalexin in wheat. Issue 1 (19th June 2013) - Du Fall, Lauren A.; Solomon, Peter S.
Summary: Stagonospora nodorum and Pyrenophora tritici‐repentis produce the effector ToxA that interacts with the dominant susceptibility gene in wheat, Tsn1 . However, the way in which ToxA induces cell death and causes disease is unclear. Here, we performed comprehensive metabolite profiling of ToxA‐infiltrated wheat ( Triticum aestivum ) to observe the secondary metabolite response to this effector. A strong induction of secondary metabolism subsequent to SnToxA infiltration was observed, including the monoamine serotonin. We established a novel role for serotonin as a phytoalexin in wheat and demonstrated that serotonin strongly inhibited sporulation of S. nodorum . Microscopy revealed that serotonin interferes with spore formation and maturation within pycnidial structures of the fungus. Subsequent analysis of S. nodorum exposed to serotonin revealed metabolites changes previously associated with sporulation, including trehalose and alternariol. Furthermore, we identified significantly lower concentrations of serotonin during infection compared with infiltration with ToxA, providing evidence that S. nodorum may suppress plant defence. This is the first study demonstrating induction of plant secondary metabolites in response to a necrotrophic effector that have significant antifungal potential against the pathogen. While it is generally accepted that necrotrophs exploit host cell responses, the current research strengthens the notion that necrotrophs require mechanisms to overcome plant defence to survive initial stages of infection.